alcides lanza’s Musical Awakening in Buenos Aires: An Interview - Goldman, Jonathan (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2007)
In this interview with Argentinean-born alcides lanza, the composer speaks about his teachers in Rosario, and his first experiments with tape music, as well as his move to Buenos Aires in 1955. He speaks about his studies at the claem of the Di Tella institute as well as his role in the establishment of the ensemble Agrupación Música Viva, and about his work as a pianist in Juan Carlos Paz’s Agrupación Nueva Música. He discusses how his contact in Buenos Aires with teachers like Maderna, Messiaen, Copland and Ginastera, and colleagues like Gandini, Kagel, Krieger and Tauriello, shaped his musical development.